Dependence Structure and Volatility Spillover Between Financial Markets of China and Other One Belt One Road Countries (Journal of Asian Development Studies, 2024)
One Belt One Road (OBOR) is an international cooperation program initiated by Xi Jinping (Chinese president) in 2013, aiming to create economic trade, promote regional cooperation, and enhance regional markets' effectiveness. OBOR covers over 70 countries (2/3 of the world's population) and approximately a third of the world's GDP (Du & Zhang, 2018). This study aims to investigate the correlations, volatility spillover, and spillback between China and OBOR initiative countries to measure the time-varying behavior in the financial markets. Two financial markets, i.e., the stock market and the foreign exchange, were selected for the study. 6x countries (each representative of one corridor) having maximum trade based on their balance of trade values were chosen for this study. DCC M GARCH model and copula were applied for this study's analysis. R programming is used for data analysis using R-studio. All sample financial markets showed an asymmetric dependence on China's financial markets, and this dependence increases during financial crises or shock periods compared to good times. All financial markets also indicated two-way time-varying volatility spillover effects in the long run. The financial crises may further intensify these spillover effects.